Crossings: Public exchange & transport interchange - Mitha, Trusha (My University, 2013)
Johannesburg is a city transforming. Like many other cities in the developed world, the traditional hierarchy of space is changing and a fragmentation of competing urban centres has resulted from this change. This thesis aims to explore the potential of transport nodes of becoming new and important places within a fragmented city. By re-conceptualising transport nodes as a latent public space, it challenges the places where transport networks cross. An investigation of various urban theorists, concerning the change of traditional city arrangements are studied in comparison to the changing urban qualities of Johannesburg. The spatial implications of Johannesburg being built on an apartheid model are also explored, as well as the impact that transport has had on the spatial geography of Johannesburg. These studies indicate the fragmented nature of the spatial form of Johannesburg and reveal the separation of activities and social groups experienced by people, based on economic class. Transport is fundamental in two ways, it has enabled decentralisation, but in this new spatial configuration, it also allows for new connections and a potential to establish new hubs of urbanised energy. The introduction of the Gautrain to transport networks in Johannesburg, allow a site to be chosen where integration or ‘crossings’ of people, culture, transport and infrastructure may be located. The location of the Marlboro Gautrain Station provides a platform to address the social inequalities experienced in public transport, through an architectural response.